SISTEM PAKAR UNTUK MENDIAGNOSIS KERUSAKAN HARDWARE KOMPUTER BERBASIS WEB PADA PT. BUKIT PUTRI HIJAU - Dian Gustina; Achmad Sumbaryadi (JURNAL MITRA MANAJEMEN, 2015)
Abstract In a common enterprise constraints that we are facing, one of which occurred on thecomputer that we use, so as to hinder our work. Moreover, not all companies areexperts to handle this problem, as well as experienced by PT. Bukit PutriHijau.Anexpert system is a computer system that matched the ability of decision-making froman expert. An emulsion is much more powerful than a simulation that just needsomething that is evident in some areas or things. Knowledge in an expert systemmay be an expert, or knowledge that is generally found in books, magazines andpeople who have knowledge about a field. The term expert systems, knowledge-basesystem, or an expert system-knowledge base, frequently used mainly in the samesense.With the expert system we hope to help address the issue of damage tocomputer hardware we have often experienced.Key Word : Expert System, Knowledge Base, Damage of Computer Hardware